2009
DOI: 10.3746/jkfn.2009.38.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anticancer Activities of Defatted Soybean Grits Fermented by Bacillus subtilis NUC1

Abstract: Antioxidant and anticancer activities of water and ethanol extracts of defatted soybean grits (DSG) fermented Bacillus subtilis NUC1 were determined and compared with those of the raw DSG. The fermented defatted soybean grits (FDSG) exhibited higher total polyphenols and flavonoids contents than DSG. The ethanol extracts of FDSG (FD-E) showed the highest polyphenol and flavonoid contents with 23.35 mg/g and 3.48 mg/g, respectively. Particularly, FD-E showed higher DPPH radical scavenging activities with RC50 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…And it has been suggested that those enhanced antioxidant activities are eventuated as flavonoid and phenols release increased by microbial enzymes structural changes in phytochemicals, respectively during the process of fermentation (Hur et al, ). Along with enhanced antioxidant activities, fermented ingredients or sources appeared to improve serum lipid profiles, antioxidant, antiproliferative, and antithrombotic activities (Lee et al, ; Ryu, Kang, & Cho, ). Improved serum lipid levels and antiplatelet aggregation activities were observed from animal models fed with Sargassum thunbergii fermented with the help of Lactobacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…And it has been suggested that those enhanced antioxidant activities are eventuated as flavonoid and phenols release increased by microbial enzymes structural changes in phytochemicals, respectively during the process of fermentation (Hur et al, ). Along with enhanced antioxidant activities, fermented ingredients or sources appeared to improve serum lipid profiles, antioxidant, antiproliferative, and antithrombotic activities (Lee et al, ; Ryu, Kang, & Cho, ). Improved serum lipid levels and antiplatelet aggregation activities were observed from animal models fed with Sargassum thunbergii fermented with the help of Lactobacillus sp.…”
Section: Introductionmentioning
confidence: 99%